Natural killer cells are pivotal for in vivo protection following systemic infection by Sporothrix schenckii - Ferreira, Lucas Souza [UNESP]; Portuondo, Deivys Leandro [UNESP]; Polesi, Marisa Campos [UNESP]; Carlos, Iracilda Zeppone [UNESP] (Wiley, 2018)
Natural killer (NK) cells are one of the first cell types to enter inflammation sites and have been historically known as key effector cells against tumours and viruses; now, accumulating evidence shows that NK cells are also capable of direct in vitro activity and play a protective role against clinically important fungi in vivo. However, our understanding of NK cell development, maturation and activation in the setting of fungal infections is preliminary at best. Sporotrichosis is an emerging worldwide-distributed subcutaneous mycosis endemic in many countries, affecting humans and other animals and caused by various related thermodimorphic Sporothrix species, whose prototypical member is Sporothrix schenckii. We show that following systemic infection of BALB/c mice with S. schenckii sensu stricto, NK cells displayed a more mature phenotype as early as 5 days post-infection as judged by CD11b/CD27 expression. At 10 days post-infection, NK cells had increased expression of CD62 ligand (CD62L) and killer cell lectin-like receptor subfamily G member 1 (KLRG1), but not of CD25 or CD69. Depletion of NK cells with anti-asialo GM1 drastically impaired fungal clearance, leading to a more than eightfold increase in splenic fungal load accompanied by heightened systemic inflammation, as shown by augmented production of the pro-inflammatory cytokines tumour necrosis factor-α, interferon-γ and interleukin-6, but not interleukin-17A, in the spleen and serum. Our study is, to the best of our knowledge, the first to demonstrate that a fungal infection can drive NK cell maturation in vivo and that such cells are pivotal for in vivo protection against S. schenckii.
Keywords: activation; maturation; natural killer cells; Sporothrix; sporotrichosis